1981
DOI: 10.3758/bf03197848
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent effects of double cuing in directed forgetting

Abstract: Previous research in directed forgetting in pigeons has focused on the effect of single forget cues (F-eues) interpolated within the retention interval in delayed matching-to-sample (DMTS). The present series of experiments focuses on the ability of a remember cue (R-cue) to cancel the effects of a previously presented forget cue both when the forget cue occurs within the retention interval and when the forget cue precedes sample presentation. In the first experiment, an R-cue decreased the effect of an F-cue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…It was found that instructional cues to forget the sample, presented during the delay interval, interfered with matching accuracy on probe trials more than did instructional cues to remember. This finding closely resembles those of other directedforgetting experiments, and suggests that event-duration memory, like memory for modal stimulus attributes, involves a process in which memory for the sample is actively processed or rehearsed (Grant, 1981(Grant, , 1984Maki, 1981), or in which the probability of retrieving the sample memory is reduced by the change in context resulting from F cue presentations (Kendrick et al, 1981 ;Stonebraker, Rilling, & Kendrick, 1981).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was found that instructional cues to forget the sample, presented during the delay interval, interfered with matching accuracy on probe trials more than did instructional cues to remember. This finding closely resembles those of other directedforgetting experiments, and suggests that event-duration memory, like memory for modal stimulus attributes, involves a process in which memory for the sample is actively processed or rehearsed (Grant, 1981(Grant, , 1984Maki, 1981), or in which the probability of retrieving the sample memory is reduced by the change in context resulting from F cue presentations (Kendrick et al, 1981 ;Stonebraker, Rilling, & Kendrick, 1981).…”
Section: Discussionsupporting
confidence: 82%
“…However, since little is known about the effects of variables other than delay length, the experiments reported here were undertaken to determine whether event-<1uration memory reacts to interference treatments in the same way as memory for modal attributes. Accordingly, two variables known to affect the amount of forgetting during the delay interval separating sample from comparison were manipulated: delay-interval illumination (e.g., Cook, 1980;Kendrick & Rilling, 1984) and the presentation during the delay of instructional cues to remember or to forget the sample (e.g., Grant, 1981;Kendrick, Rilling, & Stonebraker, 1981;Maki & Hegvik, 1980). Both variables have been shown to substantially reduce delayed matching performance with sample stimuli differing in modal stimulus attributes.…”
mentioning
confidence: 99%
“…If so, then the unexpected presentation of the comparison stimuli on F-cued probe trials should result in very poor performance because the memory trace of the sample will have dissipated entirely. Indeed, at least five studies have confirmed this prediction (Grant, 1981b;Maki & Hegvik, 1980;Maki, Olson, & Rego, 1981;Stonebraker, Rilling, & Kendrick, 1981). On the other hand, if the presentation of the F cue is withheld until the end of the retention interval, performance on probe trials should be much better.…”
Section: Directed Forgettingmentioning
confidence: 83%
“…(Bouton & Bolles, 1979;Olton, 1978;Tomie, 1976;Wagner, 1978). Recent investigations of human and animal short-term memory have indicated contextdependent retrieval in directed forgetting (Bjork & Geiselman, 1978;Kendrick et al, 1981;Stonebraker et al, 1981). Furthermore, a two-stores account of human memory with two operating processes, one for long-term memories and one for short-term memories, is no longer seriously accepted (Anderson, 1982;Lewis, 1979;Murdock 1982;Raaijmakers & Shiffrin, 1981).…”
Section: Discussionmentioning
confidence: 99%